2023
DOI: 10.1111/mec.17214
|View full text |Cite
|
Sign up to set email alerts
|

Infection with ‘Candidatus Liberibacter asiaticus’ improves the fecundity of Diaphorina citri aiding its proliferation: A win‐win strategy

Xiaoge Nian,
Yaru Luo,
Xinyu He
et al.

Abstract: The evolution of insect vector‐pathogen relationships has long been of interest in the field of molecular ecology. One system of special relevance, due to its economic impacts, is that between Diaphorina citri and ‘Candidatus Liberibacter asiaticus’ (CLas), the cause of the severe Asian form of huanglongbing. CLas‐positive D. citri are more fecund than their CLas‐negative counterparts, boosting opportunities for pathogens to acquire new vector hosts. The molecular mechanism behind this life‐history shift remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Although there is limited research on the mechanisms underlying vector-bacteria interactions. In D. citri-C Las interaction, C Las operates host hormone signaling and miRNA to mediate the mutualistic interaction between D. citri fecundity and its replication ( Nian et al, 2024 ). Singh and Linksvayer, 2020 found that Wolbachia -infected colonies of Monomorium pharaonis exhibited increased colony-level growth, accelerated colony reproduction, and shortened colony life cycles compared to uninfected colonies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is limited research on the mechanisms underlying vector-bacteria interactions. In D. citri-C Las interaction, C Las operates host hormone signaling and miRNA to mediate the mutualistic interaction between D. citri fecundity and its replication ( Nian et al, 2024 ). Singh and Linksvayer, 2020 found that Wolbachia -infected colonies of Monomorium pharaonis exhibited increased colony-level growth, accelerated colony reproduction, and shortened colony life cycles compared to uninfected colonies.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs play important roles in regulating cellular events at the post-transcriptional level during biological processes ( Bartel, 2018 ; Asgari, 2011 ; Asgari, 2014 ). For example, in D. citri-C Las interaction, C Las hijacks the JH signaling pathway and host miR-275 that targets the vitellogenin receptor ( DcVgR ) to improve D. citri fecundity, while simultaneously increasing the replication of C Las itself, suggesting a mutualistic interaction in D. citri ovaries with C Las ( Nian et al, 2024 ). In term of host-virus interactions, miR-8, and miR-429 target Broad isoform Z2 , the gene involved in the hormonal regulation of single nucleopolyhedrovirus (HaSNPV)-mediated climbing behavior in Helicoverpa armigera ( Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is limited research on the mechanisms underlying vector-bacteria interactions. In D. citri - C Las interaction, C Las operates host hormone signaling and miRNA to mediate the mutualistic interactio between D. citri fecundity and its replication [35]. Singh and Linksvayer (2020) [41] found that Wolbachia -infected colonies of Monomorium pharaonis exhibited increased colony-level growth, accelerated colony reproduction, and shortened colony life cycles compared to uninfected colonies.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs play important roles in regulating cellular events at the post-transcriptional level during biological processes [32,33,34]. For example, in D. citri - C Las interaction, C Las hijacks the JH signaling pathway and host miR-275 that targets the vitellogenin receptor ( DcVgR ) to improve D. citri fecundity, while simultaneously increasing the replication of C Las itself, suggesting a mutualistic interaction in D. citri ovaries with C Las [35]. In term of host-virus interactions, miR-8 and miR-429 target Broad isoform Z2 , the gene involved in the hormonal regulation of single nucleopolyhedrovirus (HaSNPV)-mediated climbing behavior in Helicoverpa armigera [36].…”
Section: Introductionmentioning
confidence: 99%